Redesign of Artificial Lighting with Electricity Saving Aspects - Harefa, Linwan Abadi; Feranita; Ervianto, Edy (International Journal of Electrical, Energy and Power System Engineering, 2020)
Redesign of artificial lighting with electricity saving aspects at the Putri Tujuh Ujung Batu Foundation aims to evaluate the design of artificial lighting systems in several rooms including the Inayah Islamic Elementary School Office, Putri Tujuh Orphanage Dormitory and Fastabiqul Khairat Mosque by calculating aspects of energy savings. Initial measurement results show that the lighting strength in each room does not meet the specified standards. The measurement results are evaluated using the zonal cavity method. It is recommended that the type of lamps used are 2 Philips LED 27 Watt lamps and 33 Philips LED 33 Watt lamps. Calculations with this method are simulated using the DiaLux Evo V.8.2 software which displays a three-dimensional image along with the strength of the lighting in each room. From the simulation results it was found that the use of pure white paint coated walls increases the lighting strength. The percentage of Electricity savings for Inayah Islamic Elementary School office space was 31.25%, Putri Tujuh Orphanage Dormitory was 61.64% and the Fastabiqul Khairat Mosque was 7.11% when compared to the use of Hannochs lamps.